2007
DOI: 10.1111/j.1365-2389.2007.00924.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations and modelling of the reactions of 10 metals with goethite: adsorption and diffusion processes

Abstract: A sample of goethite was mixed for periods which ranged from 2 hours to 8 weeks with solutions of dilute nitrate salts of Pb, Hg, Cd, Zn, Cu, Ni, Co, Mn, Cr and Al. The amount of sorption after each period was measured for an appropriate pH range for each metal. The sorption behaviour was characterized both by using characteristics of the sorption curves such as the pH at which half of the added metal was sorbed (pH 50 ) and by fitting a model in which sorption was mainly characterized by an affinity constant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 54 publications
4
68
0
Order By: Relevance
“…However, modeling results and their implications for the relevance of aging, hysteresis and irreversible sorption behavior may strongly depend on the metals and mineral phases under investigation. For instance, different elements may form various types of surface complexes (Garnier et al, 2006), or may be characterized by different pore diffusion rates depending on their ionic radius (Fischer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, modeling results and their implications for the relevance of aging, hysteresis and irreversible sorption behavior may strongly depend on the metals and mineral phases under investigation. For instance, different elements may form various types of surface complexes (Garnier et al, 2006), or may be characterized by different pore diffusion rates depending on their ionic radius (Fischer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, metal diffusion into goethite pores cannot be ruled out, as this has been shown to be a relevant process for other metal contaminants (Mustafa et al, 2006;Fischer et al, 2007). Previous studies focusing on Np(V) sorption onto Fe-oxide minerals suggest that the following surface chemical processes may be relevant: (1) the transformation of neptunium outer-into inner-sphere complexes, as indicated by X-ray absorption spectroscopy (Jerden and Kropf, 2007), and (2) the surface-mediated reduction of Np(V) to Np(IV), which has been reported for goethite (Jerden and Kropf, 2007) and magnetite (Nakata et al, 2002;Nakata et al, 2004).…”
Section: Relevance Of Aging Processesmentioning
confidence: 99%
“…Heavy metal adsorption on Fe and Mn oxides has been studied by several researchers and in general the studies have suggested the following order of adsorption of heavy metal ions on these oxides: Pb N CuN Mn N Co N Zn N Ni for the Mn oxides (McKenzie, 1989); CuN Pb N ZnN Co N Ni for goethite (Fischer et al, 2007), Pb N Cu N Zn N Co N Ni and PbN CuN Zn N Ni N Co for hematite and amorphous Fe, respectively (Ross, 1994). For soils, specially the highly weathered ones, the order has been, generally, Cr N Pb N Cu N CdN Zn N Ni (Matos et al, 1996;Fontes et al, 2000;Gomes et al, 2001;Fontes and Gomes, 2003).…”
Section: Metal Dispersion In the Landscapementioning
confidence: 99%
“…Zinc adsorption by soil constituents is commonly considered to be specific, i.e., its affinity to charged surfaces is considerably higher than that of other cations coexisting in the solution phase, and is characterized by higher adsorption than expected from cation-exchange reactions with soil constant-charge surfaces (Alloway, 1995). It is common for equilibrium not to be attained throughout weeks of reaction, and Zn adsorption progresses as a result of metal-ion diffusion into inner sites (Fischer et al, 2007;Li et al, 2010;Nibou et al, 2010). Tiller et al (1984a) suggested that the kinetics of specific adsorption is slower than that of nonspecific adsorption; it is more pH-dependent than, and dominates over non-specific adsorption, at low initial concentrations.…”
Section: Introductionmentioning
confidence: 98%
“…Zinc adsorption onto metal oxides and clay minerals was successfully simulated as a function of solution concentration, pH, and I by employing models based on two or three adsorption layers (Barrow et al, 1981;Fischer et al, 2007). Adsorption by soil as a function of solution concentration and pH (but not I) was simulated by a single-layer model (Gu and Evans, 2007;Saeki and Kunito, 2009), or by a phenomenological, modified Langmuir competitive-adsorption model (Bar-Yosef, 1979;Bar-Yosef et al, 1988).…”
Section: Introductionmentioning
confidence: 99%